Lavender Products Associated With Premature Thelarche and Prepubertal Gynecomastia: Case Reports and Endocrine-Disrupting Chemical Activities - Ramsey, J Tyler (J Clin Endocrinol Metab, 2019)
CONTEXT: Previous case reports associated prepubertal gynecomastia with lavender-containing fragrances, but there appear to be no reports of premature thelarche. OBJECTIVE: To add to a case series about lavender-fragranced product use and breast growth in children and to measure endocrine-disrupting chemical activity of essential oil components. DESIGN, SETTING, AND PATIENTS: Patients experiencing premature thelarche or prepubertal gynecomastia with continuous exposure to lavender-fragranced products were evaluated in the pediatric endocrinology departments of two institutions. Mechanistic in vitro experiments using eight components of lavender and other essential oils were performed at National Institute of Environmental Health Sciences. MAIN OUTCOME MEASURES: Case reports and in vitro estrogen and androgen receptor gene expression activities in human cell lines with essential oils. RESULTS: Three prepubertal girls and one boy with clinical evidence of estrogenic action and a history of continuous exposure to lavender-containing fragrances were studied. Breast growth dissipated in all patients with discontinuation of the fragranced products. Some of the components tested elicited estrogenic and antiandrogenic properties of varying degrees. CONCLUSION: We report cases of premature thelarche that resolved upon cessation of lavender-containing fragrance exposure commonly used in Hispanic communities. The precise developmental basis for such conditions could be multifactorial. In vitro demonstration of estrogenic and antiandrogenic properties of essential oil components suggests essential oils in these cases could be considered a possible source and supports a possible link with idiopathic prepubertal breast development. Whether the level of lavender oil estrogenic potency is sufficient to cause these effects is unknown.